Bureaucratic Pathology in Investment Permit Granting Procedures in Central Java Province - Jeni Minan; Feri Fadli Rizki; Hayatun Nufus (HK-Publishing, 2026)
Abstract In the current bureaucratic process in Indonesia, weaknesses in the service sector are still often found, these weaknesses include complicated services, inefficient services, and a lack of fairness in service delivery. This study aims to analyze the procedures for granting investment permits to minimize the occurrence of bureaucratic pathology and to analyze the steps taken by the Central Java government if bureaucratic pathology occurs in Central Java Province. This study is a qualitative descriptive study. Data collection was carried out using interview, observation, and documentation techniques. The results of this study indicate that in the DPMPTSP of Central Java Province there are still services that have not been running optimally, namely existing infrastructure, employee time discipline, and late issuance of permits. Meanwhile, the obstacle is the public who wants things to be immediate. To overcome this, the DPMPTSP of Central Java is innovating and reforming the bureaucracy. Keywords: Bureaucracy, Investment, Pathology, Public Services, Abstrak Dalam proses birokrasi saat ini di Indonesia, kelemahan di sektor pelayanan masih sering ditemukan; kelemahan tersebut meliputi layanan yang rumit, layanan yang tidak efisien, serta kurangnya keadilan dalam pemberian layanan. Penelitian ini bertujuan untuk menganalisis prosedur pemberian izin investasi guna meminimalkan terjadinya patologi birokrasi serta menganalisis langkah-langkah yang diambil oleh pemerintah Jawa Tengah jika terjadi patologi birokrasi di Provinsi Jawa Tengah. Penelitian ini merupakan penelitian deskriptif kualitatif. Pengumpulan data dilakukan dengan menggunakan teknik wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa pada DPMPTSP Provinsi Jawa Tengah masih terdapat layanan yang belum berjalan optimal, yaitu terkait infrastruktur yang ada, kedisiplinan waktu pegawai, dan keterlambatan penerbitan izin. Sementara itu, kendala yang dihadapi adalah adanya keinginan masyarakat agar segala sesuatu dapat diselesaikan secara instan. Untuk mengatasi hal tersebut, DPMPTSP Jawa Tengah melakukan inovasi dan reformasi birokrasi. Kata kunci: Birokrasi, Investasi, Patologi, Pelayanan Publik.